2017
DOI: 10.1073/pnas.1707853114
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of UCP1 using CRISPR/Cas9 in the white adipose tissue of pigs decreases fat deposition and improves thermogenic capacity

Abstract: Uncoupling protein 1 (UCP1) is localized on the inner mitochondrial membrane and generates heat by uncoupling ATP synthesis from proton transit across the inner membrane. UCP1 is a key element of nonshivering thermogenesis and is most likely important in the regulation of body adiposity. Pigs (Artiodactyl family ) lack a functional UCP1 gene, resulting in poor thermoregulation and susceptibility to cold, which is an economic and pig welfare issue owing to neonatal mortality. Pigs also have a tendency toward fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
124
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 64 publications
7
124
0
Order By: Relevance
“…36 Furthermore, lack of UCP-1 in pigs may also affect body composition. 37 In the present study, we found that FGF21 treatment improved glucose tolerance and increased insulin sensitivity. Notably, the acute blood glucose-lowering effect of FGF21 is abolished in UCP-1 knockout mice, 38 indicating UCP-1 involvement in the mechanism.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…36 Furthermore, lack of UCP-1 in pigs may also affect body composition. 37 In the present study, we found that FGF21 treatment improved glucose tolerance and increased insulin sensitivity. Notably, the acute blood glucose-lowering effect of FGF21 is abolished in UCP-1 knockout mice, 38 indicating UCP-1 involvement in the mechanism.…”
Section: Discussionsupporting
confidence: 59%
“…Unfortunately, knowledge regarding the effect of food restriction on body composition in obese minipigs is limited, but in humans, the percentage of total weight loss comprising fat free mass varies from 4% to 53%, depending on the intervention . Furthermore, lack of UCP‐1 in pigs may also affect body composition …”
Section: Discussionmentioning
confidence: 99%
“…Although we did not observe a clear correlation between the absence of PKD1 and appearance of multilocular cells within subcutaneous depot of adipose tissue, the protein abundance of UCP1 was clearly elevated in the absence of PKD1. Of note, in several other mouse models, increased UCP1 abundance was observed in unilocular adipocytes (Rossmeisl et al , ; Schneider et al , ; Zheng et al , ). However, in isolated PKD1‐deficient adipocytes we observed elevated gene expression of Adrb3, but Ucp1 levels were not altered at basal conditions.…”
Section: Discussionmentioning
confidence: 94%
“…However, whether and how this translates to adaptation strategies for domestic poultry production remains to be explored. Zheng et al (2017) [26] find that genetic trait modification can decrease low-temperature susceptibility and that there is substantial potential to explore this, as CC portends changes but there has been little recent work on animal climate resilience.…”
Section: Non-ruminantsmentioning
confidence: 99%